Костные остатки льва из энеолитических поселений Северо-Западного Причерноморья - Бибикова, В.И. (Вестник зоологии, 1973)
The article deals with the description of lion bones found during excavations of eneolithic settlements in Odessa region of the Ukraine. Settlements belong to the culture of Gumelnitsa (town of Bolgrad) and Late Tripolie (vil. Mayaki) and are dated by the end of the IV—III millenium B. C. Accompanying fauna permits imagining the landscape conditions: open dry steppes, alternating with the plots of broad-leaved forests along the river and on ravine slopes. Findings of lion remains in the North-Western Black Sea outline a part of the ancient area of this species.